National and subnational mortality of urological cancers in Iran, 1990–2015. Issue 2 (1st October 2018) - Pishgar, Farhad; Amini, Erfan; Gohari, Kimiya; Aminorroaya, Arya; Sheidaei, Ali; Rostamabadi, Yasna; Ebrahimi, Hooman; Yoosefi, Moein; Naderimagham, Shohreh; Rezaei, Nazila; Modirian, Mitra; Namazi Shabestari, Alireza; et al.
Abstract: Purpose: To study trends of urological cancers mortalities in Iran between 1990 and 2015 as a part of a larger project named national and subnational burden of diseases, injuries, and risk factors. Methods: The primary dataset of this project comprises data of national death registration system. Cause‐specific mortality fraction for each age, sex, province, and year group was calculated using a two‐stage mixed effects and spatiotemporal models, and then these fractions were applied to all‐cause mortality rates, obtained from a parallel study to estimate mortality rates attributable to each cause. Results: In 2015, urological cancers constituted 8% of cancer‐related deaths in Iran, and number of deaths due to prostate, bladder, testicular, and kidney and other urinary organs cancers were estimated as 2, 128 (1, 565–2, 891), 297 (230–385), 301 (144–639), and 195 (143–267), respectively. Our estimates show that age‐standardized death rates (ASDRs) of these cancers reached 6.8 (5–9.23), 0.47 (0.37–0.61), 0.96 (0.46–2.04), and 0.24 (0.18–0.33) deaths per 100, 000 individuals in 2015, a reduction in the three latter cancers, from 4.09 (2.92–5.76), 13.04 (10.04–16.95), 1.23 (0.46–3.34), and 1.76 (1.28–2.42) deaths per 100, 000 individuals in 1990, respectively. Conclusions: In conclusion, despite disparities among different provinces, overall mortality rate of urological cancers decreased significantly since 1990s in Iran.